Sistem Pendukung Keputusan Seleksi Penyiaran Berita Menggunakan Metode Profile Matching - Ira Puspita Sari; Al Amin (Journal of Applied Computer Science and Technology, 2020)
TVRI Riau-Kepri difficulties in news investigasion process that will be providedto the public riau-kepri. Based on the obserpasion that researchers do in TVRI riau-kepri seen that the shophiscation that of the technology has not been fully utilizet well by tvri riau-kepri so the difficualty in selecting news. That prosess will use a variety of alternative action which may be selected whit the expectation produce the best decision to give the news can be use method profile matching which is aprosess comparingthe value of the actual data of a profile that will be in grades whit the value profile is expented, So as to know that difference in competence the smaleer gap produced the greater weight the selection of news will be broadcast whit the highest rating based on criteria of news. That has been set, and 3 dicision that is good, enough and less.